Response of chickpea crop to foliar spray with zinc in combination with different levels of phosphorus and sulphur as soil application - Fathi, Abdel Moniem I.; EI Desouky, Hamdi I.; Kandel, Nadia Kh. (2007)
A field experiment was conducted on a sandy soil at Ismailia Agric. Res. Station, Egypt during the winter season of 2005/2006 to study the effect of phosphorus, sulphur and zinc and their interaction on seed and straw yields of chickpea (Giza 3 var) and its nutrient contents. Treatments comprised a combination of three doses of phosphorus (0, 20 and 40 kg P20s/fed), sulphur (0, 200 and 400 kg S/fed) and zinc (0, 150 and 300 g Zn/fed).
Includes reference.
Summary in Arabic.
1
Keywords: Chickpea -- Fertilizers; Foliar feeding; Plants -- Effect of zinc on; Plants -- Effect of phosphorus on; chickpea -- Effect of sulfur on